Sunway Campus Library: innovating for service excellence - Wong, Sook Jean; Sinnasamy, Janaki; Goh, Wei Haan; Rusli, Mohammad Faiz (Universiti Teknologi MARA, Kedah, 2017)
Sunway College, established in 1987, evolved into two institutions, i.e. Sunway University and Sunway College KL in 2011. Along this journey, the Library started out as Tun Hussein Onn Library in 1987, and transformed itself into a modern learning commons with the name “Sunway Campus Library” in 2015. The display will highlight the innovations and changes which took place over the last 3 years beginning with the move to a new library in 2015. From a small college library, Sunway Campus Library now has state-of-the-art services and facilities of a modern academic library. The Library features a beautiful fountain area within, thus creating a relaxing and conducive study environment for its students. It caters to a variety of learning styles, from individual quiet and silent study spaces to collaborative zones, training rooms and group project pods for group discussion. Other facilities include WiFi, an extended hour area open till 2 am, a drink and phone area, self-check and return stations, instructional lab, computer clusters, audiovisual viewing zone and printing stations. New customeroriented services also include online surveys, online feedback for Help Desk, Orientation and Research skills sessions, online booking of facilities, and an Academic Language Learning Service geared to helping students in academic writing. Innovative services and facilities such as; (i) Real time feedback for Research and Information Skills sessions and Reference enquiries at Help Desk, (ii) Reciprocal borrowing services with Monash University Malaysia, (iii) Beautiful fountain area within the library creating a relaxing and conducive study environment, (iv) Academic Language Learning Service with the collaboration of English Language academics to assist students in their academic writing, and (v) Response to students’ feedback and complaints within two days.